Research on heat transfer characteristic of crude oil during the tubular heating process in the floating roof tank. (September 2017) - Zhao, Jian; Dong, Hang; Wang, Xiulian; Fu, Xiaoming
Abstract: By means of finite volume method, the heat transfer characteristic of crude oil under the tubular heating in the floating roof tank is investigated by numerical simulation. The evolution of temperature profile and its relationship with the flow pattern is presented in detail. A noticeable finding is that there exists the transformation of the flow pattern which affects the temperature profile apparently during the heating process. Special concern is taken on the evolution of temperature distribution on the interface between oil and the inner wall of the tank. The temperature profile on the top wall, sidewall and base wall of the tank is investigated. It is concluded that the plume induced by natural convection takes most responsibility for the formation of temperature field in the tank. The second factor is the boundary condition of the tank.